1984
DOI: 10.1111/j.1365-2605.1984.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of seminal free L(‐) carnitine in fertile and infertile men

Abstract: Data about the levels of free L-carnitine, an epididymal marker in human semen, are contradictory and unclear, particularly in their relationship to fertility. This can perhaps be explained by the absence of any studies of seminal L-carnitine in a large group of fertile men, and by the lack of consideration of factors influencing its secretion. In this study, free L-carnitine was determined using a spectrophotometric method in deproteinized semen samples from fertile (n = 162) and infertile men without azoospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 18 publications
0
5
1
1
Order By: Relevance
“…Our study observed a mean total carnitine concentration of 60.49 mg/ml. Other researchers observed total carnitine values ranging from 0.2 to 1.3 mM (0.03-0.21 mg/ml) (2,30,31). We measured carnitine by HPLC, using a C 18 column and absorption at 215 nm.…”
Section: Carnitinementioning
confidence: 99%
“…Our study observed a mean total carnitine concentration of 60.49 mg/ml. Other researchers observed total carnitine values ranging from 0.2 to 1.3 mM (0.03-0.21 mg/ml) (2,30,31). We measured carnitine by HPLC, using a C 18 column and absorption at 215 nm.…”
Section: Carnitinementioning
confidence: 99%
“…Acetyl‐L‐carnitine is the prominent carnitine in spermatozoa and its concentration was lower in semen of infertile men (Kohengkul et al. , 1977; Soufir et al. , 1984).…”
Section: Food Supplementationmentioning
confidence: 99%
“…La carnitine libre et I'acetyl Lcarnitine jouent un rble important dans la maturation postgonadique des spermatozo'fdes des mammiferes [32], et le quotient acetyle L-carnitine/carnitine etait different dans de spermatozo'fdes de bonne ou de mauvaise qualite [3,22]. L'acetyle L-carnitine est la carnitine dominante dans les spermatozoYdes et sa concentration etait inferieure dans le sperme d'hommes infertiles [36,64]. La concentration de carnitine libre dans le plasma seminal etait en correlation significative avec la concentration et la motilite spermatiques [48], et il a ete possible de stimuler la motilite des spermatozoYdes en ajoutant de racetyle carnitine in vitro [68].…”
Section: Carnitineunclassified